PERANAN PEMOLISIAN MASYARAKAT TERHADAP PEMBINAAN SISTEM KEAMANAN LINGKUNGAN DALAM PENCEGAHAN DAN PENANGGULANGAN TINDAK PIDANA KEJAHATAN DI WILAYAH POLISI SEKTOR RUMBAI PESISIR - Firman Tambunan; Mukhlis R; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
According to experts, crime is all of human behavior that contrary to law, beconvicted, which is set in the criminal law. Crimes committed in the District ofRumbai Pesisir increased. The crimes included defamation, assault, two-wheeledmotor vehicle theft, larceny, theft with violence and others. However, the minimumnumbers of members of the Police Sector of Rumbai Pesisir cause low performanceof police in dealing with a criminal offense that occurred. Therefore it needs anactive role in prevention and mitigation of crimes. This is manifest in the PoliceRegulation No. 7 of 2008 on Community Policing. As a strategy which is a model ofpolicing that emphasizes on equal partnership between the police and localcommunities, to overcome any problems that threaten the security and orderliness,are called the Police Community Partnership Forum (FKPM). The purposes of thisthesis are: First, to determine the effectiveness of the Role of Community Policing indeveloping of Security System in the Prevention and Control of EnvironmentalCrimes in Police Jurisdiction of Rumbai Pesisir Sector. Second, to determine the roleof Community Policing Efforts toward the Development of Environmental SecuritySystem Crime Prevention and Criminal Jurisdiction Police Sector in Rumbai Pesisircould run with the maximum.Type of the research is the study of empirical sociological or juridical.Location of the study is Police Sector of Rumbai Pesisir. Sources of data were theprimary data and secondary data consisting of primary legal materials, secondaryand tertiary, while the techniques of data collection are interviews / interviews andreview of literature. After collecting the data, the writer analyzed qualitatively byusing the deductive method by analyzing the problems of a general nature and thenspecifically drawn to the conclusion based on existing theories.From the research problem, there are two things that can be inferred, First,The Role of the Community Policing Development Environment Security System inPrevention of Crimes in Police Jurisdiction Rumbai Pesisir Sector by coordinatingand socialize the application of community policing. Second, the roles of CommunityPolicing Efforts toward the Development of Environmental Security System CrimePrevention and Criminal Jurisdiction Police Sector in Rumbai Pesisir by attemptingto coordinate well, trying to improve the professionalism, asking for people’s activeparticipation, propose improvements and facilities to socialize. The writer advices,first, improves the implementation of community policing, increasing the intensity ofsocialization and counseling to FKPM and society. Second, actualize the goodcoordination, increase professionalism in the implementation of community policingactivities.Keywords : Roles - Community Policing - Security - Crime